Vitamin D, Gestational Diabetes, and Measures of Glucose Metabolism in a Population-Based Multiethnic Cohort - Åse Ruth Eggemoen; Christin Wiegels Waage; Line Sletner; Hanne L. Gulseth; Kåre I. Birkeland; Anne Karen Jenum (Journal of Diabetes Research)
Objective. We explored associations between maternal 25-hydroxyvitamin D (25(OH)D) status during pregnancy and gestational diabetes (GDM) and other measures of glucose metabolism. Methods. We analysed 25(OH)D at 15 and 28 gestational weeks (GW) in 745 multiethnic pregnant women attending antenatal care units in Oslo, Norway, between 2008 and 2010. GDM was diagnosed with a 75 g oral glucose tolerance test at 28 GW. Separate regression analyses were performed to investigate associations between 25(OH)D and GDM and measures of glucose metabolism. Results. A higher proportion of ethnic minority women had GDM (p<0.01) and low 25(OH)D (p<0.01) compared to Europeans. In logistic regression analyses, 25(OH)D < 50 nmol/L was associated with GDM after adjusting for age, parity, education, and season (OR 1.6; 95% CI 1.1–2.2). After additional adjustments for variables reflecting fat mass (skinfolds or BMI) and ethnicity, the association disappeared with ethnicity having a much stronger effect than the adiposity variables. We got similar results exploring effects on other measures of glucose metabolism and when change in 25(OH)D from inclusion to 28 GW was taken into account. Conclusions. Vitamin D deficiency was not associated with GDM or glucose metabolism in a multiethnic population-based study, after adjustments for confounding factors, in particular ethnicity.